2014
DOI: 10.1111/1462-2920.12411
|View full text |Cite
|
Sign up to set email alerts
|

Systems‐level analysis of the metabolic responses of the diatom Phaeodactylum tricornutum to phosphorus stress

Abstract: SummaryPhosphorus is an important macronutrient. To understand the molecular and cellular responses to phosphorus stress better, transcriptome profiling in combination with biochemical investigations was conducted in the model diatom Phaeodactylum tricornutum. Out of 10 402 predicted genes, 2491 and 405 genes were significantly upregulated or downregulated respectively. Unsurprisingly, genes associated with phosphate uptake were upregulated, such as the phosphate transporters and alkaline phosphatases. Genes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
98
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 50 publications
18
98
2
Order By: Relevance
“…3), indicating that AP activity is higher in cells under conditions of low phosphate concentrations. Th ese results agree with previous studies (González-Gil et al 1998;Beardall et al 2001;Dyhrman & Palenik 2001;Moser et al 2010;Yang et al 2014), since this microalgae is able to use a strategy of organic phosphorus incorporation when the inorganic form of this nutrient is limited (Rengefors et al 2001;Nedoma et al 2003). On the other hand, the control and F treatment and Ub7 (B) in Control (C), F and F/8 treatments.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…3), indicating that AP activity is higher in cells under conditions of low phosphate concentrations. Th ese results agree with previous studies (González-Gil et al 1998;Beardall et al 2001;Dyhrman & Palenik 2001;Moser et al 2010;Yang et al 2014), since this microalgae is able to use a strategy of organic phosphorus incorporation when the inorganic form of this nutrient is limited (Rengefors et al 2001;Nedoma et al 2003). On the other hand, the control and F treatment and Ub7 (B) in Control (C), F and F/8 treatments.…”
Section: Resultssupporting
confidence: 92%
“…4), which suggests increased uptake of phosphate by this algae. Intraspecifi c variation in AP activity in P. tricornutum has been previously reported, hence this microalgae is used worldwide in bioassays of algal growth potential (Yang et al 2014 and references therein). Lin et al (2013) observed that P. tricornutum growing in a starved medium had intense AP activity from the fourth to the seventh day of incubation, and that AP mRNA expression was abundant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations